Influence of certain carbon and nitrogen sources on antagonistic potentiality of Trichoderma harzianum and Bacillus subtillus against Botrytis allii the incitant of onion neck rot - Sayed, Amani A.; Abd-El- razik, A. A.; Abd-El- Rahman, T. M.; Eraky, Amal (Journal of Phytopathology and Disease Management, 2014)
Gliotoxin Fermentation Agar (GFA) Medium and Nutrient Glucose Agar (NGA) medium with different carbon and nitrogen sources were used to study the impact of carbon and nitrogen sources on Trichoderma harzianum Rifai and Bacillus subtillus Cohn antagonistic efficiency against growth of Botrytis allii Munn. Results indicated that Trichoderma harzianum gave the highest inhibition % in growth of Botrytis allii when Sucrose was used as a carbon source while the lowest values of inhibition% were appeared by application of Mannitol as a carbon source. Trichoderma harzianum gave the highest inhibition% in growth of B.allii when use Potassium nitrate as a nitrogen source while the lowest values of inhibition% in growth of B.allii were obtained by application of Beef extract as a nitrogen source. Results showed also that Bacillus subtillus gave the highest inhibition% in growth of B.allii when Mannitol was used as a carbon source while the lowest values of inhibition% in growth of B.allii were appeared by application of Sucrose as a carbon source. Bacillus subtillus gave the highest inhibition% in growth of B.allii when use Glutamic acid as a nitrogen source while the lowest values of inhibition% in growth of B.allii were appeared by application of Tryptophan as a nitrogen source.